Changes of abdominal wall tension across various resistance exercises during maximal and submaximal loads in healthy adults: a cross-sectional study - Roman Jurik; Petr Stastny; Dominik Kolinger; Tomas Vetrovsky; Jakub Novak; Alena Kobesova; Michal Krzysztofik; Andrew Busch (BMC Sports Science, Medicine and Rehabilitation)
Abstract Introduction Resistance exercises are effective for maintaining health and activating stabilizing muscles, as they trigger abdominal wall tension responses. This study compared the effects of multi-joint and single-joint, upper-body and lower-body exercises (Lat pulldown, Rows, Peck deck, Chest press, Biceps curls, Triceps extensions, French-Press, Step up, Hip abduction/adduction, Squat, Leg press, Romanian deadlift, Hamstring curls) performed at maximal and submaximal intensities. Methods This cross-sectional study included 12 men and 18 women (age:47.8 ± 5.9 years, height:174.8 ± 10.2 cm, weight: 77.7 ± 15.4 kg, BMI:25.3 ± 3.6), who wore a noninvasive sensor Ohmbelt to measure abdominal wall tension performing exercises at 15 repetition maximum (RM), 10RM, 5RM, and 1RM. Differences across exercises and sex were compared by Friedman test with Durbin-Conover post-hoc, and intensities were analyzed by Wilcoxon test. Results The study found significant differences (p < 0.05) in abdominal wall tension changes based on the type of exercise and training intensity. Multi-joint lower-body exercises, such as the Romanian deadlift, dumbbell front squat, and leg press, led to the greatest increases in abdominal tension in both sexes in comparison to single-joint upper-body exercises. Males had higher abdominal wall tension changes than females (p < 0.05) at 1RM, 5RM, and 10RM. However, no significant difference was found at 15RM, indicating that lower intensities produce similar abdominal wall tension changes in both sexes. Conclusions This study showed that multi-joint lower-body exercises were found to produce greatest abdominal wall tension increases, especially compared to single-joint upper-body exercises. The abdominal wall tension was higher in males than females due to higher loads, emphasizing the need for exercise-specific approaches.